2004
DOI: 10.1128/jvi.78.11.5612-5618.2004
|View full text |Cite|
|
Sign up to set email alerts
|

T-Cell Epitopes in Severe Acute Respiratory Syndrome (SARS) Coronavirus Spike Protein Elicit a Specific T-Cell Immune Response in Patients Who Recover from SARS

Abstract: The immunogenicity of HLA-A2-restricted T-cell epitopes in the S protein of the Severe acute respiratory syndrome coronavirus (SARS-CoV) and of human coronavirus strain 229e (HCoV-229e) was analyzed for the elicitation of a T-cell immune response in donors who had fully recovered from SARS-CoV infection. We employed online database analysis to compare the differences in the amino acid sequences of the homologous T epitopes of HCoV-229e and SARS-CoV. The identified T-cell epitope peptides were synthesized, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
97
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 27 publications
5
97
0
1
Order By: Relevance
“…The SARS-CoV infects epithelial cells in the respiratory tract causing interstitial pneumonia and elicits strong immune responses (58). Memory or surviving effector CTLs against S978 and S1203 epitopes have been reported to be detectable from SARS-recovered donors 2 mo after the onset of disease (31). In this study, CTLs still existed in the donors 7-8 mo after SARS-CoV infection and were presumably from the memory CTL pool.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The SARS-CoV infects epithelial cells in the respiratory tract causing interstitial pneumonia and elicits strong immune responses (58). Memory or surviving effector CTLs against S978 and S1203 epitopes have been reported to be detectable from SARS-recovered donors 2 mo after the onset of disease (31). In this study, CTLs still existed in the donors 7-8 mo after SARS-CoV infection and were presumably from the memory CTL pool.…”
Section: Discussionmentioning
confidence: 55%
“…A 193-aa small fragment within the S1 domain (S318 -510) was identified as a minimal receptor domain and contained multiple conformationdependent epitopes that induce highly potent neutralizing Abs (29,30). Recently, three S protein-derived CTL epitopes SSp-1 (S1167), S987, and S1203 were identified by two groups (31,32). These epitopes, however, were all screened from nonamer libraries.…”
mentioning
confidence: 99%
“…Moreover, the HLA-A2-restricted T-cell epitopes in the S2 domain of SARS-CoV could elicit T-cell immune response in donors who had fully recovered from SARS-CoV infection (Wang et al, 2004). This means that although the S2 subunit makes few contributions to inducing virus-neutralizing antibodies, we should not absolutely give up using it as a full or partial candidate antigen before obtaining protection results.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-associated lymphopenia has also been well documented (8 -10), but the underlying mechanism remains unknown. Some previous studies demonstrated the absolute counts of lymphocytes and lymphocyte subsets to be a useful indicator in the development of effective methods of diagnosis and treatment of SARS (11,12), and three HLA-A*0201-restricted CD8 ϩ T cell epitopes, SSp-1, S978, and S1202, were recently identified from SARS-CoV spike protein (13)(14)(15).…”
mentioning
confidence: 99%
“…Although memory T cell responses to epitopes S1202 and S978 were detected in an IFN-␥ ELISPOT assay in PBMCs from HLA-A*0201 ϩ recovered SARS patients up to 3 mo postinfection (14,15), how long this immunity will last requires further monitoring. Surprisingly, in the generation of effector CTLs from healthy donors without any contact history with SARS-CoV following in vitro repeated challenge of PBMCs with heat-inactivated SARSCoV-pulsed dendritic cells in culture medium supplemented with IL-7, IL-10, and IL-2, inactivated SARS-CoV provoked recall-like T cell responses in certain healthy donors, which hints that there might exist memory T cell populations cross-reactive to SARSCoV.…”
mentioning
confidence: 99%